Cryptocurrency Exchange Selection Decision Support System Using Preference Selection Index - Prasetyo, Dwi; Ariati, Nining; Lubis, Harmoko; Akbar, Aswin (SaNa: Journal of Blockchain, NFTs and Metaverse Technology, 2023)
Cryptocurrency trading is a very popular business of buying and selling digital money today. Many investors trade cryptocurrency assets through cryptocurrency exchange platforms in the hope of getting a large profit difference. However, the cryptocurrency trading business is not always favourable for investors as choosing the wrong cryptocurrency exchange can result in huge losses from the trades made. Based on these problems, it is necessary to have a decision support system for selecting the most relevant cryptocurrency exchange to be used as a cryptocurrency trading platform that can increase the chances of investors making profits. The decision support system method used in this research is Preference Selection Index (PSI). The results of the selection of cryptocurrency exchanges using the Preference Selection Index (PSI) method in this study recommend Indodax as the most relevant cryptocurrency exchange used by investors to gain profits in running a cryptocurrency trading business because it gets the highest value (0.893662729) compared to 4 other alternatives.